Geospatial Mapping and Predictive Analysis for Drug Trafficking Intervention in Eastern Indonesia - Ismail, Ismail; Felecia, Felecia; Azizah, Anisa Kurniatul; Rahmawati, Diana (West Science Interdisciplinary Studies, 2025)
This study explores the application of geospatial mapping and predictive analysis in efforts to combat drug trafficking in Eastern Indonesia—a region characterized by complex geography and limited surveillance infrastructure. Using a qualitative approach, data were collected through in-depth interviews with three key informants: a regional police officer, a representative of the National Narcotics Agency (BNN), and a local community leader. The results reveal four central themes: the current state of drug trafficking in the region, the potential and underutilization of geospatial tools, the lack of predictive analytics at the regional level, and significant challenges such as limited infrastructure, lack of trained personnel, and poor inter-agency coordination. While the use of geospatial and predictive technologies remains nascent, stakeholders express optimism about their potential. The study highlights the need for context-specific strategies, local capacity-building, and multi-stakeholder collaboration to enhance data-driven interventions in narcotics control.